Morphometric alterations of cerebellum induced by subchronic cadmium intoxication: the protective role of a soybean diet - Martin Molinero, Glenda Daniela (2021)
Cadmium (Cd) is an environmental contaminant. The aim of this study was to characterize its toxicity in cerebellum and the potential reversal by avegetarian based diet. We determined the Cd levels in total blood, metals trace and Cd concentration in tissue, and also performed morphometric andstereological analysis. Female Wistar rats (12 animals/group) were fed with casein (Cas) and soybean diets (So) as protein source for 60 days.Simultaneously, half of the animals were administered either 15 ppm of Cd in water or water as control ad libitum. Morphometric analysis includedquantifying the number of granule cell neurons (CGn) and Purkinje cells neurons (Pkn) in serial 20 μm-thick sections stained with cresyl violet alongdifferent lobules. We performed a three-dimensional volumetric reconstruction of the tissue and further quantification of the number of neuronsthrough the use of a software Stereo Investigator. The thicknesses of the molecular and granular layers of the cerebellar cortex of lobules I-X weredetermined on digital images of 3 regions of each lobule and were analyzed with IMAGE J Software. Metal concentration was determined with anICP-MS. Cd levels in total blood were incremented in CasCd vs. CasCo (P < 0.01) and in SoCd vs. SoCo (P < 0.05). Cd concentration in tissue wasincreased in CasCd vs. CasCo and vs. SoCd (P < 0.0001), with no significant differences between soy groups. Also, the trace elements wereunbalanced along the Cd intoxication. Regarding selenium levels, a significant increase was observed in the SoCd group vs. CasCd. Likewise,manganese and zinc concentrations were significantly increased in CasCd vs. its control and vs. SoCd (P < 0.0001), while there were no differencesbetween soy groups. In the case of copper, a significant increase was observed in the CasCd group vs. its control (P < 0.01) and vs. SoCd (P < 0.05).We found that sub chronic Cd exposure induces a decrease in the number of CGn in the CasCd groups vs. CasCo group (P < 0.05) and SoCd group(P < 0.01). On the contrary, the number of Pkn remained unchanged. In addition, Cd intoxication significantly reduced the internal granular layer ofCasCd group vs. SoCd group in all the lobules tested, meanwhile no effect was observed in the thickness of the molecular layer. The thicknesses ofthe different regions of each folium from cerebellar lobules I-X did not show significant differences between the groups. Overall, these resultsunmask an irreversible toxic effect of low dose sub chronic Cd intoxication on cerebellum and identify a protective role by soy-enriched diet withpotential as a therapeutic strategy for those individuals exposed to this dangerous environmental contaminant.